AI and Blockchain in Financial Data Transfer: Enhancing Efficiency, Security, and Compliance - Srianusha Kuchipudi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The financial services industry is experiencing a transformative revolution in data transfer systems by integrating artificial intelligence and blockchain technologies. This comprehensive analysis explores the challenges faced by traditional financial institutions in managing high-speed data transfers while optimizing efficiency, and maintaining security and regulatory compliance. The study examines the evolution from legacy systems to modern infrastructure, highlighting how AI-powered solutions optimize data routing and transfer efficiency while blockchain technology ensures security and integrity. Through an investigation of real-world implementations, the research demonstrates how combining AI and blockchain creates robust, efficient, and secure data transfer mechanisms that reshape the financial sector's operational capabilities. The analysis provides detailed insights into performance improvements, security enhancements, and operational efficiencies achieved through these technological integrations.
Keywords: Financial Data Security; AI Optimization; Blockchain Technology; Regulatory Compliance; Digital Transformation